Teresita Martínez-Vergne. "Shaping the Discourse on Space: Charity and Its Wards in Nineteenth-Century San Juan, Puerto Rico". Austin: University of Texas Press, 1999, 235 pp. - Froysland, Hayley S. (Fronteras de la historia, 2000)
.